WAYS OF ADAPTATION OF FOREIGN EXPERIENCE OF DIGITAL TRANSFORMATION OF LOCAL SELF-GOVERNMENT IN UKRAINE (Coordinates of Public Administration, 2026)
The article examines the digital transformation of local government as a complex management process that involves profound institutional changes in the functioning of local authorities, decision-making models, the organization of public service provision, and forms of interaction with territorial communities. It is argued that the digitalization of local government cannot be reduced to the implementation of individual information and communication technologies or electronic services, but should be considered as a component of a systemic reform of public administration.The study analyzes scientific approaches to understanding digital transformation in public administration and legal discourses, and also summarizes the regulatory and legal principles of digital development of local government in Ukraine. Particular attention is paid to the analysis of strategic and conceptual documents that determine the directions of digitalization of e-government, e-services, and e-democracy at the local level.An analysis of foreign experience in the digital transformation of local self-government was carried out, in particular, the practices of institutional integration of local authorities into national digital systems, standardization of administrative procedures, development of digital participation of citizens and ensuring the continuity of management activities in crisis conditions. Based on a comparative analysis, it was substantiated that the effectiveness of digital transformations in foreign countries is due to the combination of technological solutions with organizational and personnel changes.Ways of adapting foreign experience in the digital transformation of local self-government to Ukrainian realities were determined, taking into account decentralization processes, uneven capacity of territorial communities, limited resources and the effects of martial law. It was emphasized that in conditions of military threats, the digital transformation of local self-government acquires additional security significance, as it ensures the administrative stability of communities, data protection and continuity of public services. A conclusion was drawn about the need to form an adaptive model of digital local self-government, focused on the long-term development and European integration of Ukraine.